The Effect of Variations in the Water-to-Coffee-Powder Ratio on the Water Content and Caffeine Content of Sigarar Utang Instant Arabica Coffee - Nasution, Ananta Mulia Alfatah; Ngatirah; Oktavianty, Herawati; Nasution, Nanda Eska Anugrah (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
The Sigarar Utang Arabica coffee is a varietal of Arabica coffee that originated from the North Tapanuli region of the North Sumatra province. The purpose of this study is to see how variations in water-to-coffee powder ratios affect water content and caffeine content of Sigarar Utang Arabica instant coffee. This study's research design is a complete block design (CBD). Experiments were carried out at 95°C with three levels of coffee powder-to-water ratio: N1 (1:4)%, N2 (1:6)%, and N3 (1:8)%. Each treatment was repeated twice, for a total of six experimental units. According to the findings of this study, variations in the water-to-coffee powder ratio in Sigarar Utang coffee had a substantial impact on both moisture content and caffeine content.